Imaging the healing murine myocardial infarct in vivo: ultrasound, magnetic resonance imaging and fluorescence molecular tomography. Issue 3 (20th February 2013) - Gray, Gillian A.; White, Christopher I.; Thomson, Adrian; Kozak, Agnieszka; Moran, Carmel; Jansen, Maurits A.
<x xml:space="preserve">Abstract</x> Improved understanding of the processes involved in infarct healing is required for identification of novel therapeutic targets to limit infarct expansion and consequent long‐term ventricular remodelling after myocardial infarction. Infarct healing can be modelled effectively in murine models of coronary artery ligation. While imaging the murine heart is challenging due to its size and high rate of contraction, advances in preclinical imaging now permit accurate assessment of myocardial structure and function in vivo after myocardial infarction. Furthermore, rapid development of a range of molecular probes for use in a number of imaging modalities allows more detailed in vivo analysis of processes, including inflammation, fibrosis and angiogenesis. Here we consider the practical application of in vivo imaging by magnetic resonance imaging, ultrasound and fluorescence molecular tomography for assessment of infarct healing in the mouse.